2008
DOI: 10.3315/jdcr.2008.1020
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy findings of alopecia areata in an African-American patient

Abstract: This case shows that skin color may affect dermoscopic findings in alopecia areata. In our African-American patient with alopecia areata dermoscopy showed a diffuse honeycomb-like pigmented network, which was previously considered characteristic for androgenic alopecia and white dots, which were considered characteristic for cicatricial alopecia. Further studies are needed to elucidate the presence of white dots in alopecia areata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 7 publications
4
44
0
Order By: Relevance
“…Other dermoscopic features of alopecia areata are the same as in Caucasian and Asian patients and include exclamation mark hairs, broken hairs, black dots, circle hairs, and coudability [4,16,17,29] (Fig. 5).…”
Section: Nonscarring Alopeciasmentioning
confidence: 96%
See 2 more Smart Citations
“…Other dermoscopic features of alopecia areata are the same as in Caucasian and Asian patients and include exclamation mark hairs, broken hairs, black dots, circle hairs, and coudability [4,16,17,29] (Fig. 5).…”
Section: Nonscarring Alopeciasmentioning
confidence: 96%
“…Yellow dots are uncommon, as empty follicles appear white instead of yellow [26,29]. Although some researchers (Bapu et al [31], Mane et al [32], and Guttikonda et al [33]) reported yellow dots as the most common dermoscopic feature of alopecia areata in dark-skinned Indian patients, their pictures document white rather than yellow dots.…”
Section: Nonscarring Alopeciasmentioning
confidence: 99%
See 1 more Smart Citation
“…Yellow dots were the sensitive markers for the diagnosis of AA [9,10]. However, yellow dots did not reflect AA activity [13]. Of vellus hairs, we included only dystrophic (cadaverized) vellus hairs in the category of hair loss.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Dermoscopy of scalp disorders has been performed in our Hair Diseases Clinic with a handheld dermoscope (DermLite II ProHR 3Gen [3Gen; San Juan Capistrano, CA] attached to a Sony Cybershot digital camera [DSC-W55; Sony; Tokyo, Japan; 310-30 magnification]).We have observed small pinpoint white dots regularly distributed on the scalp of patients with Fitzpatrick skin phototypes V and VI and in sunexposed areas of patients with phototypes III and IV. These structures were seen in normal scalps and in patients with frontal fibrosing alopecia (FFA; Fig 1), lichen planopilaris (LPP), alopecia areata, androgenetic alopecia (AGA), and central centrifugal cicatricial alopecia (CCCA).…”
mentioning
confidence: 95%